Psychometric Properties of Korean Version of Self-Efficacy of Evidence-Based Practice Scale - Eui Geum Oh, RN, PhD (Asian Nursing Research, 2016)
Purpose: This study is to evaluate the psychometric properties of the Korean version of the Self-Efficacy of Evidence-Based Practice (SE-EBP) scale, which was originally developed by Chang and Crowe. The beta-version of the SE-EBP is a modified version of the original SE-EBP, which measures the clinical nurses' confidence in finding, appraising, and implementing evidence into practice. Although the original SE-EBP has been validated, no study has been conducted to validate the Korean version of SE-EBP. Methods: The original scale was translated into Korean through a process of forward and back translation of the original scale. After getting confirmation of the equivalence of the Korean forward translation by the original author, exploratory factor analysis and confirmatory factor analysis of data from 212 clinical nurses were used to test construct validity. Internal consistency was examined using Cronbach α coefficients. For the statistical analysis, STATA version 13.0 software program was used. Results: Exploratory factor analysis of the 28 items revealed three factors with eigenvalues above 1, accounting for 60.2% of the total variance. Confirmatory factor analysis showed good fit of the three-factor structure which was statistically significant (χ2=718.61, df=330, p<.01). For internal consistency, Cronbach α coefficient for the total scale was .95, and it was greater than .80 for each of the three subscales. Conclusions: The Korean version of SE-EBP scale showed evidence of adequate construct validity and reliability. This study might have contributed to a wider application of the SE-EBP scale, but further studies are needed to provide more evidence on the structure of the scale.